2014
DOI: 10.1080/02705060.2014.970672
|View full text |Cite
|
Sign up to set email alerts
|

Impact of water depth and sediment type on root morphology of the submerged plantVallisneria natans

Abstract: The environment of Lake Taihu has changed a great deal in recent decades. Wetland plant restoration is considered an efficient way to keep it healthy. However, restoration efforts are affected by environmental factors which have important influences on wetland plant growth. In order to study the mutual effects of water depth and sediment type on the growth of aquatic plants, the impacts of the two environmental factors on root morphology of the submerged plant Vallisneria natans were investigated in an outdoor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…After 36 days of plant growth, roots had abundantly developed over the whole planar optode foil. The main root-parameters such as diameter, length and surface area were 0.3 mm, 53.4 mm and 16.3 cm 2 , respectively (see Table S2), which is similar to previous studies (Liu et al, 2014;Bai et al, 2015), indicating the plant health of Vallisneria spiralis accompanied by the planar optode was slightly affected over the entire experiment.…”
Section: General Features Of Sediment and Root Developmentsupporting
confidence: 88%
“…After 36 days of plant growth, roots had abundantly developed over the whole planar optode foil. The main root-parameters such as diameter, length and surface area were 0.3 mm, 53.4 mm and 16.3 cm 2 , respectively (see Table S2), which is similar to previous studies (Liu et al, 2014;Bai et al, 2015), indicating the plant health of Vallisneria spiralis accompanied by the planar optode was slightly affected over the entire experiment.…”
Section: General Features Of Sediment and Root Developmentsupporting
confidence: 88%
“…Water depth had major effects on plant size and reproductive output. In a previous study, V. natans attained maximum total biomass and leaf mass at 60 cm, whether in clay or sandy loam 28 . However, in the present study, maximum biomass of V. natans was obtained at 100 cm, perhaps due to water clarity.…”
Section: Discussionmentioning
confidence: 67%
“…It increased with increasing depth until 5.5 m and then gradually decreased at deeper sites. V. natans may shift the light compensation point to cope with reduced light (Bai et al, 2015; Wei et al, 2018). Blanch (1998) found that V. natans had a low photosynthetic light intensity compensation point of 9.4 umol m −2 s −1 , which is close to the light intensity value (9.0 umol m −2 s −1 ) at 5.5 m water depth in our in situ physiological response experiment.…”
Section: Discussionmentioning
confidence: 99%